1975
DOI: 10.1210/jcem-40-4-670
|View full text |Cite
|
Sign up to set email alerts
|

A Diphasic Pattern of Gonadotropin Secretion in Patients with the Syndrome of Gonadal Dysgenesis

Abstract: Cross sectional and longitudinal studies of plasma FSH and LH in 58 patients, age 2 days of 20 yr, with the syndrome of gonadal dysgenesis show a diphasic pattern of gonadotropin secretion. The mean basal plasma FSH level is 43 plus or minus 7 (SE) ng/ml (LER-869) in patients from 2 days to 4 yr, which is strikingly elevated. Thereafter, a decline in plasma FSH to a mean level of 4 plus or minus 0.7 (SE) ng/ml occurs between 4 and 10 yr, followed by a rise after 10 yr to 61 plus or minus 4 (SE) ng/ml. The patt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
107
3
2

Year Published

1978
1978
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 271 publications
(125 citation statements)
references
References 9 publications
13
107
3
2
Order By: Relevance
“…Consistent with the X chromosome rearrangement, endocrine studies showed FSH-dominant hypergonadotropic hypogonadism, which has been reported in Turner syndrome with gonadal dysgenesis (16), and FISH analysis revealed SHOX duplication on the idic(X) chromosome. Thus, this female represents a further case with the combination of SHOX overdosage and gonadal estrogen deficiency.…”
Section: Discussionsupporting
confidence: 71%
“…Consistent with the X chromosome rearrangement, endocrine studies showed FSH-dominant hypergonadotropic hypogonadism, which has been reported in Turner syndrome with gonadal dysgenesis (16), and FISH analysis revealed SHOX duplication on the idic(X) chromosome. Thus, this female represents a further case with the combination of SHOX overdosage and gonadal estrogen deficiency.…”
Section: Discussionsupporting
confidence: 71%
“…Elevated gonadotrophin levels and slow skeletal maturation suggest that oestrogen deficiency in Turner girls begins already in infancy (38,39). Oestrogen may also have positive behavioural and neurocognitive effects in the developing brain (40,41).…”
Section: Considerations In Different Diagnostic Groupsmentioning
confidence: 99%
“…That the plasma concentrations of LH and FSH in castrated rams also varied with age suggests that changes in the secretion of the gonadotrophins can occur independently of the hormones secreted by the testes and this has been demonstrated previously. In agonadal children (Conte et al 1975, Reiter & Grumbach 1981 and in castrated male Rhesus monkeys (Plant 1980), the FSH and LH levels were high for 2 years post-partum, then declined and rose again about the time puberty would have occurred. A similar phase of elevated FSH secretion was noted in castrated rams at 5 weeks of age (Olster & Foster 1986).…”
Section: Discussionmentioning
confidence: 99%